2021
DOI: 10.55002/mr.1.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Food grade vinegar acts as an effective tool for short-term meat preservation

Abstract: The study was designed to evaluate the physico-chemical, microbial and sensorial quality of beef incorporated with different levels of vinegar at refrigerated storage (4±1ºC). Fresh beef samples were divided into three different batches i.e. T0 = control (without vinegar), T1 = 5% vinegar and T2 = 10% vinegar. The samples were evaluated for sensory properties (color and flavor), physico-chemical properties (pH, cooking loss, FFA, POV and TBARS) and microbial counts (TVC, TCC and TYMC) on 0, 7 and 14 days of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
6
19
0
Order By: Relevance
“…Yadav et al (2018) found a significant increase in TBARS value of control and fiber enriched sausage with an increase in storage period. Similar findings were reported by Sarker et al (2021) in goat meat sausage during refrigerated storage.…”
Section: Thiobarbituric Acid Value (Tbars)supporting
confidence: 90%
See 1 more Smart Citation
“…Yadav et al (2018) found a significant increase in TBARS value of control and fiber enriched sausage with an increase in storage period. Similar findings were reported by Sarker et al (2021) in goat meat sausage during refrigerated storage.…”
Section: Thiobarbituric Acid Value (Tbars)supporting
confidence: 90%
“…The rise in the pH (P<0.05) of the control samples may be caused by bacterial consumption of acids produced during the breakdown of proteins due of the depletion of the stored glucose. The last increase in pH levels might have been caused by release of ammonia molecules from endoprotease or proteolytic microbial flora in the raw meat (Sarker et al, 2021;Ali et al, 2022).…”
Section: Ph Valuementioning
confidence: 99%
“…In recent years, interest has increased in the quality attributes of food (Farmer et al, 1997). Generally, consumers prefer to have high quality, convenient and safe meat products that contain natural flavor and taste (Saba et al, 2018;Khatun et al, 2022;Hossain et al, 2021;Islam et al, 2021;Sarker et al, 2021).The present study was carried out to compare the meat yield and quality characteristics of meat from indigenous, cockerel and sonali chicken of about similar body weight.…”
Section: Introductionmentioning
confidence: 96%
“…Meat processing industries needs accurate, faster, real-time, low-cost and non-chemical technologies for quality detection. To reduce economic losses during processing, meat industry has to supply high-quality products consistently and quality control procedures must be carried out (Liao et al, 2010;Akhter et al, 2020;Lina et al, 2020;Sarker et al, 2021). Hence, quality assurance and control are the main tasks in production and processing of meat and meat products.…”
Section: Introductionmentioning
confidence: 99%